2008
DOI: 10.1007/s11274-008-9844-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of antioxidative defense system in the copper and temperature acclimated strains of Anabaena doliolum

Abstract: This study provides first hand comparative account of growth and antioxidative defense system of the wild type, Cu 2? and temperature treated wild type and acclimated strains of Anabaena doliolum Bharadwaja against Cu 2? and high temperature. The acclimated strains showed perceptible growth at 250 lM Cu 2? and 47°C temperatures, respectively. In contrast to this the wild type strain on exposure to 50 lM Cu 2? and 47°C temperature depicted almost complete inhibition of growth. However, the peroxide content was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
2
0
0
Order By: Relevance
“…Lipid peroxidation is commonly caused by increased ROS production (Meng et al, 2015), which generates an imbalance in the cellular redox state and is accompanied by increased MDA content (Bhandari and Sharma, 2006). Similar to our results, several researchers have observed increased lipid peroxidation in photosynthesizing organisms exposed to different bioactive compounds (He and Häder, 2002;Yu et al, 2003;Mishra et al, 2008;Li et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Lipid peroxidation is commonly caused by increased ROS production (Meng et al, 2015), which generates an imbalance in the cellular redox state and is accompanied by increased MDA content (Bhandari and Sharma, 2006). Similar to our results, several researchers have observed increased lipid peroxidation in photosynthesizing organisms exposed to different bioactive compounds (He and Häder, 2002;Yu et al, 2003;Mishra et al, 2008;Li et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, it has been reported that elevated Cu levels have an inhibitory effect on CAT activity [43]. Similar responses in CAT activity have also been described in several studies [44][45][46].…”
Section: Discussionsupporting
confidence: 81%